Association of Blood MCP-1 Levels with Risk of Obstructive Sleep Apnea: A Systematic Review and Meta-Analysis - Mohammad Moslem Imani; Masoud Sadeghi; Mehdi Mohammadi; Annette Beatrix Brühl; Dena Sadeghi-Bahmani; Serge Brand (Medicina, 2022)
Background and objective: Among the broad variety of chemokines, monocyte chemoattractant protein-1 (MCP-1) is considered to be one of the most important chemokines. Among others, MCP-1 activates monocytes and other immune cells highly involved in inflammation. In the present systematic review and meta-analysis, we evaluated the relationship between serum/plasma MCP-1 levels and the risk of obstructive sleep apnea (OSA) in adults as a disease related to inflammation. Materials and methods: Four databases were systematically investigated until 12 July 2022. We used the Review Manager 5.3 software (Copenhagen: The Nordic Cochrane Centre, The Cochrane Collaboration, Copenhagen, Denmark) to extract and calculate the standardized mean difference (SMD) and its 95% confidence interval (CI) of plasma/serum levels of MCP-1 between adults with and without OSA. Results: Eight articles including eleven studies in adults were entered into the meta-analysis. The serum/plasma MCP-1 levels in adults with OSA were higher than that in the controls (SMD = 0.81; p = 0.0007) and as well as for adults with severe OSA compared to those with mild and moderate OSA (SMD = 0.42; p < 0.0001). The subgroup analysis showed that ethnicity was an effective factor in the pooled analysis of blood MCP-1 levels in adults with OSA compared to the controls (Asians: (p < 0.0001), mixed ethnicity: (p = 0.04), and Caucasians: (p = 0.89)). The meta-regression showed increasing serum/plasma MCP-1 levels in adults with OSA versus the controls, publication year, age of controls, body mass index (BMI) of controls, and sample size reduced, and also BMI and the apnea–hypopnea index of adults with OSA increased. Conclusions: The meta-analysis showed that compared to the controls, serum/plasma levels of MCP-1 in adults with OSA were significantly more, as well as adults with severe OSA having more serum/plasma MCP-1 levels compared to the adults with mild to moderate OSA. Therefore, MCP-1 can be used as a diagnostic and therapeutic factor in adults with OSA.